Effect of Mg Content on the Properties of Al-Zn-In-Mg-Ti-Ga-Mn Sacrificial Anode - SONG Qing-yuan, ZHANG Hai-bing, MA Li, SUN Ming-xian (Cailiao Baohu)
For improving the comprehensive performance of Al sacrificial anode, the electrochemical properties evaluation test, electrochemical impedance test, polarization test, metallographic analysis and micro-area potential distribution analysis were used to study the influence of content of Mg element on Al-Zn-In-Mg-Ti-Ga-Mn sacrificial anode, and the suitable content of Mg element in Al sacrificial anode was confirmed. esults showed that with the increase of Mg content, the actual capacity of the sacrificial anode was improved. The change of Mg content mainly affected the performance of the sacrificial anode by affects the grain size of the sacrificial anode and the amount / distribution of interior precipitates. When the Mg content was 0.8%, the Al-Zn-In-Mg-Ti-Ga-Mn sacrificial anode had better performance.